Membangun Kemandirian dan Kesejahteraan Umat Melalui Usaha Penanaman Sayur Hidroponik - Sampelan, Anna B.; Sipayung, Rismaida H.; Tarihoran, Emmeria (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2024)
In contemporary times, the issues of community independence and welfare are crucial and require special attention. Dependence on conventional employment makes society vulnerable to economic shocks. Therefore, sustainable solutions such as hydroponic vegetable cultivation, a soil-less farming method using nutrient solutions with water as the medium, are needed. Hydroponics is very suitable for limited spaces and offers many benefits, such as water conservation and quick, high-quality yields. In this research, the author uses a qualitative method with a literature review approach, collecting and processing data to propose hydroponics as a solution to improve the independence and welfare of urban communities. By utilizing a carefully designed 10-step pastoral strategy, which provides a suitable framework for implementation within the community, people can be trained and educated to use this farming technique to increase food production, income, and local food security. Additionally, hydroponics can create new job opportunities.